Experimental investigations of bond behavior of double-row spliced rebars in Ultra-High Performance Concrete (UHPC). (1st June 2023) - Hu, Xinyu; Xue, Weichen; Lv, Yanheng; Mao, Jize
Highlights: Double-row spliced specimens are designed and tested under direct tension. Bond-slip relationship and bond strength of spliced rebars are discussed. Bond stress distribution of rebars with strain gauges inside is determined. Design recommendation for critical splice length of rebars in UHPC is presented. Abstract: The paper aims to evaluate the bond behavior of spliced rebars in Ultra-High Performance Concrete (UHPC). A total of 27 double-row spliced specimens were prepared and tested under direct tension where the test variables covered bar diameter (14 mm and 25 mm) and splice length (2 db, 4 db, 6 db and 8 db ). The failure mode, crack pattern, bond-slip relationship, bond strength, and bond stress distribution were determined and discussed. Three failure modes including rebar pullout, rebar rupture and UHPC splitting were observed. Owing to the bridge action of steel fibre in the post-cracking phase, the splitting failure was ductile. The bond strength decreased as the splice length and bar diameter increased. For db of 14 mm, the bond strength of specimens with splice lengths of 4 db, 6 db and 8 db dropped by 30.9 %, 40.6 % and 50.1 % than that with a splice length of 2 db, respectively. Under various splice lengths, the bond stress presented uniform distribution, single peak distribution and bimodal distribution profiles. Moreover, the design recommendation for the critical splice length of rebars in UHPC was presented and compared with the current specifications.